MicroRNA-148b targets the TGF-β pathway to regulate angiogenesis and endothelial-to-mesenchymal transition during skin wound healing - Miscianinov, V; Martello, A; Rose, L; Parish, E; Cathcart, B; Mitić, T; Gray, GA; Meloni, M; Zen, A; Caporali, A (Elsevier, 2018)
Transforming growth factor beta (TGF-β) is crucial for regulation of the endothelial cell (EC) homeostasis. Perturbation of TGF-β signaling leads to pathological conditions in the vasculature, causing cardiovascular disease and fibrotic disorders. The TGF-β pathway is critical in endothelial-to-mesenchymal transition (EndMT), but a gap remains in our understanding of the regulation of TGF-β and related signaling in the endothelium. This study applied a gain- and loss-of function approach and an in vivo model of skin wound healing to demonstrate that miR-148b regulates TGF-β signaling and has a key role in EndMT, targeting TGFB2 and SMAD2. Overexpression of miR-148b increased EC migration, proliferation, and angiogenesis, whereas its inhibition promoted EndMT. Cytokine challenge decreased miR-148b levels in ECs while promoting EndMT through the regulation of SMAD2. Finally, in a mouse model of skin wound healing, delivery of miR-148b mimics promoted wound vascularization and accelerated closure. In contrast, inhibition of miR-148b enhanced EndMT in wounds, resulting in impaired wound closure that was reversed by SMAD2 silencing. Together, these results demonstrate for the first time that miR-148b is a key factor controlling EndMT and vascularization. This opens new avenues for therapeutic application of miR-148b in vascular and tissue repair.